Student Assessment of Worship Facilities in Higher Education - Uldiman Uldiman; Indiani Hasanah Putri; Uccy Adeh Putri; Hafizul Hamdi (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to explore students' assessments of worship facilities in higher education. This research uses a quantitative method with a survey approach, data sources were taken using a questionnaire from one hundred and thirty respondents who were students from twenty-nine universities in Indonesia, and analyzed using descriptive analysis techniques using SPSS version 20 software. The results of the analysis show that students agree with the fifteen indicators for assessing worship facilities in higher education, the fifteen assessment indicators are; i) The mosque/prayer room has a comfortable atmosphere for worship; ii) The mosque/prayer room has a sturdy building structure; iii) The design of the mosque/prayer room is good and beautiful; iv) The interior design of the mosque/prayer room is well arranged; v) The lighting in the mosque and its surroundings is good; vi) The mosque room is spacious and can accommodate many people; vii) The prayer equipment provided for mosque congregations is sufficient (for example, mukena and prayer mats); viii) The prayer rows are arranged neatly so that it is easier for the congregation to worship; ix) Cleanliness inside and outside the mosque/prayer room is maintained; x) Cleanliness of prayer equipment (mukena, prayer mat) provided by the mosque/prayer room is maintained; xi) The mosque/prayer room has a clean ablution area; xii) Mosques/prayer rooms have clean toilets; xiii) The security facilities in the mosque/prayer room are adequate; xiv) The safety of the congregation's belongings is guaranteed at the mosque/prayer room; and xv) Mosque/prayer room staff are friendly to the congregation. Overall, students agree with all points of the worship facilities assessment. Worship facilities at universities are considered to be good and can support the congregation in carrying out worship solemnly to Allah.